Strategi Pengembangan Destinasi Wisata Berbasis Folklor (Ziarah Mitos: Lahan Baru Pariwisata Indonesia) - Tri Amanat (Sekolah Vokasi, Universitas Gadjah Mada, 2019)
The tourism sector is a national priority in the 2015-2019 RPJM of the Jokowi-JK government. Various parties can play an active role in opening new tourist destinations, both at local, regional, and even international levels. Many myths and legends in the community that can be used as a basis for determining the development of new tourist sites. This study used descriptive qualitative method. Recommendation material for regional selection / selection to be developed as folklore-based tourist destinations can be applied in the form of categories. The category in question is adapted from Irina-Maria Necheş (2013) as follows; the presence or absence of tangible and intangible values to be appointed, the classification of the principal values to be raised, whether mythological, religious, or historical. In other words, the effort to form an image as a regional tourism selling power in question is developed based on cultural ideas (which can be abstract) and then concretized so that visitors can enjoy them sensually.